Agaritine derived from Agaricus blazei Murrill induces apoptosis via mitochondrial membrane depolarization in hematological tumor cell lines - Atsushi Ogasawara; Hiroki Doi; Taei Matsui; Etsuko Tokunaga; Masao Amakawa; Hidehiko Akiyama (Fujita Medical Journal, 2023)
Objectives: Agaritine (AGT) is a hydrazine-containing compound derived from the mushroom Agaricus blazei Murill. We previously reported the antitumor effect of AGT on hematological tumor cell lines and suggested that AGT induces apoptosis in U937 cells via caspase activation. However, the antitumor mechanism of AGT has not been fully understood.